2022
DOI: 10.1021/acs.est.2c03319
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Amino Acids with Ferrate(VI): Impact of the Carboxylic Group on the Primary Amine Oxidation Kinetics and Mechanism

Abstract: Ferrate (Fe(VI)) is a novel oxidant that can be used to mitigate disinfection byproduct (DBP) precursors. However, the reaction of Fe(VI) with organic nitrogen, which is a potential precursor of potent nitrogenous DBPs, remains largely unexplored. The present work aimed to identify the kinetics and products for the reaction of Fe(VI) with primary amines, notably amino acids. A new kinetic model involving ionizable intermediates was proposed and can describe the unusual pH effect on the Fe(VI) reactivity toward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…Fe­(VI)-based advanced oxidation processes may involve active species such as Fe­(IV), Fe­(V), O 2 , H 2 O 2 , OH·, and O 2 ·– through self-decomposition of Fe­(VI) in aqueous solution. , Moreover, CO 3 ·– might be produced in the NaHCO 3 /Fe­(VI) process. PMSO was used as a probe to investigate the active species. , Fe­(IV)/Fe­(V) converts PMSO to PMSO 2 , whereas other active species cause PMSO to form polymeric and/or hydroxylated products but not PMSO 2 . As shown in Figure a and Figure S4 (Fe­(VI) alone), all the PMSO was transformed into PMSO 2 , which demonstrated that Fe­(IV)/Fe­(V) were the only reactive species in the three processes.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…Fe­(VI)-based advanced oxidation processes may involve active species such as Fe­(IV), Fe­(V), O 2 , H 2 O 2 , OH·, and O 2 ·– through self-decomposition of Fe­(VI) in aqueous solution. , Moreover, CO 3 ·– might be produced in the NaHCO 3 /Fe­(VI) process. PMSO was used as a probe to investigate the active species. , Fe­(IV)/Fe­(V) converts PMSO to PMSO 2 , whereas other active species cause PMSO to form polymeric and/or hydroxylated products but not PMSO 2 . As shown in Figure a and Figure S4 (Fe­(VI) alone), all the PMSO was transformed into PMSO 2 , which demonstrated that Fe­(IV)/Fe­(V) were the only reactive species in the three processes.…”
Section: Resultsmentioning
confidence: 53%
“…PMSO was used as a probe to investigate the active species. 37,38 Fe(IV)/Fe(V) converts PMSO to PMSO 2 , whereas other active species cause PMSO to form polymeric and/or hydroxylated products but not PMSO 2 . 39 As shown in Figure 2a and Figure S4 (Fe(VI) alone), all the PMSO was transformed into PMSO 2 , which demonstrated that Fe(IV)/ Fe(V) were the only reactive species in the three processes.…”
Section: Validation Of Reactive Species During Lev Oxidationmentioning
confidence: 99%
“…The peroxyl radical produced from the addition of O 2 to the C-centered radical undergoes O 2 •– elimination followed by the formation of imine , and carbinolamine that then undergoes deammonification to simultaneously produce NH 4 + and methional (Figure ). …”
Section: Resultsmentioning
confidence: 99%
“…Compared with radicals, high-valent metals generally have a higher steady-state concentration and better selectivity toward micropollutants due to targeting their electron-rich moieties. Furthermore, high-valent metal species may resist the influence of matrices in the treatment of real water samples. High-valent iron (Fe­(IV)/Fe­(V), ferrate­(VI) (Fe VI O 4 2– )) species usually selectively react with contaminants with phenolic, nitrogen-containing, or sulfur-containing functional groups , while exhibit low reactivity toward merely aliphatic or aromatic compounds. For instance, benzoic acid, a commonly used probe compound and typical structure in natural organic matter, is inert to high-valent iron but susceptible to oxidation by nonmetallic radicals, including HO • , SO 4 •– , and Cl • . ,, In addition, unlike radicals susceptible to scavenging by halides, , ferrate­(VI) exhibits relatively low reactivity to bromide and almost no reactivity to chloride, hence mitigating the formation of toxic halogenated byproducts. , …”
Section: Introductionmentioning
confidence: 99%